2018
DOI: 10.1111/eci.12903
|View full text |Cite
|
Sign up to set email alerts
|

Upregulated N‐cadherin expression is associated with poor prognosis in epithelial‐derived solid tumours: A meta‐analysis

Abstract: BackgroundN‐cadherin is an important molecular in epithelial‐mesenchymal transition (EMT) and has been reported to be associated with aggressive behaviours of tumours. However, prognostic value of N‐cadherin in solid malignancies remains controversially.Materials and MethodsThe Pubmed/MELINE and EMBASE databases were used for a comprehensive literature searching. Pooled risk ratio (RR) and hazard ratio (HR) with their corresponding 95% confidence intervals (CIs) were employed to quantify the prognostic role.Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 73 publications
1
29
0
Order By: Relevance
“…In various malignancies including breast cancer, cells acquire motility and invasiveness by upregulating N-cadherin during EMT [27][28][29]. We also reported that N-cadherin is associated with tumor aggressiveness in esophageal carcinoma [30], and others demonstrated the value of N-cadherin as a marker of invasive, malignant tumors [29,31], supporting our finding that N-cadherin expression in PB may be a predictive biomarker of NM. The expression level of N-cadherin may represent the real-time metastatic potential of tumor cells ( Figure 3e).…”
Section: Discussionsupporting
confidence: 86%
“…In various malignancies including breast cancer, cells acquire motility and invasiveness by upregulating N-cadherin during EMT [27][28][29]. We also reported that N-cadherin is associated with tumor aggressiveness in esophageal carcinoma [30], and others demonstrated the value of N-cadherin as a marker of invasive, malignant tumors [29,31], supporting our finding that N-cadherin expression in PB may be a predictive biomarker of NM. The expression level of N-cadherin may represent the real-time metastatic potential of tumor cells ( Figure 3e).…”
Section: Discussionsupporting
confidence: 86%
“…Aberrant N-cadherin expression has a clear role in tumour progression in epithelial cancer cells and has been associated with poor overall patient survival in diverse types of cancers [38]. Accordingly, we have found that the presence of leader mesenchymal cells, either N+ cancer cells or CAFs, is significantly associated with distant metastasis and low overall survival in patients with head and neck SCC.…”
Section: Discussionmentioning
confidence: 66%
“…We also observed that D14 and D15 downregulate vimentin , N-cadherin , Slug , and β-catenin gene expression, especially in p53-expressing osteosarcoma cells. A high expression of these genes is associated with cancer metastasis and poor prognosis [ 40 , 41 , 42 , 43 ]. On the other hand, the inhibition of vimentin , N-cadherin , Slug , and β-catenin can reduce invasion, migration, and metastases development [ 44 , 45 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%